Aktivitas Government Public Relations dalam Mengelola Diseminasi Informasi City Branding Kota Pekanbaru - Fadmi Nanda Putri; Welly Wirman; Muhammad Firdaus (Jurnal Riset Komunikasi, 2021)
The implementation of government public relations in the Pekanbaru City Government is carried out by the Public Relations of the Regional Secretariat and the Information Division of Public Communication, Diskominfosantik, in which two different divisions carry out the same task and function, namely government public relations activities. However, the Pekanbaru City Government has succeeded in maximizing its efforts to disseminate information on city branding with one of the most active media centers in Indonesia. This research uses descriptive qualitative research methods, with interview and observation techniques, and uses data analysis techniques Huberman Miles. The results of this study explain that government public relations activities at City Government Public Relations are applied to the management of information dissemination through media relations, to build Regional Head personal branding based on mediascape analysis of Pekanbaru City, while the IKP Division conducts information dissemination through the media center to build Regional Head personal branding and OPD corporate branding through actively published live news release content. The management of the two communication channels refers to setting the intermedia agenda.